Social Media Usage Impacts on SME’s Firm Performance: Evidence From West Java, Indonesia - Noviaristanti, Siska; Shinta Ceysaria Yunita; Sunu Puguh Hayu Triono (School of Business, IPB University (SB-IPB), 2023)
This study aims to answer two questions, namely whether social media usage affects the firm performance of Small Medium Enterprise (SME), and what factors encourage SME to use social media. Using path analysis, this study proves that social media usage has a positive significant influence on firm performance of SME. While using the Technological-Organizational-Environmental (TOE) framework, it was found that organizational factor has the greatest positive influence on social media usage. Environmental factor are the second biggest factor that encourages SME to use social media. While the technological factor is the least factor that influence SME to use social media. This research was conducted in 300 SMEs in West Java, Indonesia, and involved various business sectors ranging from food and beverage to automotive. The findings of this study contribute to the academic discussion of strategic entrepreneurship on the relationship between social media usage and firm performance. The findings of this study can also provide direction to examine how is the mechanism of the relationship between social media usage and firm performance of SME. Keywords: social media usage, TOE framework, firm performance, SME